The Impact of Remittances on Rural Poverty and Inequality in China - Zhu, Nong (World Bank, Washington, DC, 2012)
Large numbers of agricultural labor moved from the countryside to cities after the economic reforms in China. Migration and remittances play an important role in transforming the structure of rural household income. This paper examines the impact of rural-to-urban migration on rural poverty and inequality in the case of Hubei province using the data of a 2002 household survey. Since remittances are a potential substitute for farm income, the paper presents counterfactual scenarios of what rural income, poverty, and inequality would have been in the absence of migration. The results show that, by providing alternatives to households with lower marginal labor productivity in agriculture, migration leads to an increase in rural income. In contrast to many studies that suggest the increasing share of non-farm income in total income widens inequality, this paper offers support for the hypothesis that migration tends to have egalitarian effects on rural income for three reasons: (i) migration is rational self-selection - farmers with higher agricultural productivities choose to remain in local agricultural production while those with higher expected return in urban non-farm sectors migrate; (ii) poorer households facing binding constraints of land shortage are more likely to migrate; and (iii) the poorest poor benefit disproportionately from remittances.